Pendidikan Kesehatan Pemeriksaan Payudara Sendiri (Sadari) Terhadap Pengetahuan, Sikap, dan Tindakan Remaja Putri - Saputra, Andre Utama; Ariyani, Yulinda; Arsi, Ranida (Socius: Jurnal Penelitian Ilmu-Ilmu Sosial, 2024)
Breast cancer does not only occur in developed countries but also in developing countries such as Indonesia. Breast cancer ranks 8th of all cancers in Indonesia. Breast cancer is also a major concern, because it is the most common type of cancer in women. This Community Service aims to determine breast self-examination health education (BSE) on the knowledge, attitudes and actions of young women at SMK Kader Bangsa Palembang. Community Service Method with pretest posttest. Remja are teenagers with a menstrual cycle of 7-10 days with a total of 26 vocational school students who meet the inclusion criteria. The test used was the Wilcoxon Sign Runk Test with p0.05 using a computer. The results of the study showed that breast self-examination health education (BSE) had an effect on knowledge p value (0.0000.05), attitude p value (0.003)(0.05), action p value (0.004)(0.05) . Conclusion of breast self-examination health education (BSE) on the knowledge, attitudes and actions of young women at SMK Kader Bangsa Palembang. It is hoped that the suggestions for female students can be used as management of the BSE technique to detect early signs and symptoms of breast cancer.